SOCIAL MEDIA LEARNING AND NETWORK CONFIGURATION - Usman Arif (International Journal of Contemporary Issues in Social Sciences, 2024)
The social media learning is an emerging trend in e learning for case studies and analytical reasoning . The latest trends in LinkedIn , Twitter, YouTube , MacAfee, Google and Yahoo provide information and knowledge that foster creativity by sharing data and knowledge across multiple fields of studies. The network configuration plays a vital role in emerging technologies in location and data sharing . The networks connectivity of WIFI, GSM , GPRS and 5G are all configured by mobile internet. The new trends develop case based studies for data modeling and data simulation for connecting online puzzles , videos and demonstration of logic for analytical reasoning . The students interact with online quizzes like puzzles and video games in developing skills that enables them in future productivity. The computer applications provide human computer interactions HCI for GUIs , TEL learning , graphical , posters , demonstration , videos , animations and interaction with digital methodologies of online learning in social media. The article will provide the details of use of social media in e learning and also the network configuration through intelligent means like small details included in message auto request ARQ headers for configuration . The networks can shift among themselves through Internet protocols.